Determination of Mineral Contents in Dehydrated Egg Powder by ICP-OES - Kumaravel, S.; Paranthaman, R.; Amutha, S. (Asian Journal of Chemistry, 2014)
Quantitative analyses were conducted on four different dehydrated egg powders. The essential elements i.e., phosphorous, calcium, iron, magnesium, potassium, sodium and zinc, essential trace elements (selenium, copper, chromium, manganese) and potentially toxic, elements (arsenic, cadmium, lead, mercury) were determined by ICP-OES. The method was optimized and evaluated with the use of certified reference material. Inorder to evaluate the mineral content in the egg powders, microwave digestion was used to digest the sample. The results in the whole egg powder (mg kg–1) were: As 0.163, Se 102.6 ± 1.0, Zn 36.35, P 804.5 ± 2.0, Pb 1.131, Fe 123.8 ± 5.0, Mg 458.9 ± 5.0, Ca 1123 ± 2, Na 241.2 ± 1 and K 439 ± 3. It was concluded that, for most essential elements, dehydrated egg powder contribute to mineral nutrition and play a key role in the human nutrition's.